Economic Growth in the 1990s : Learning from a Decade of Reform - World Bank (Washington, DC: World Bank, 2012)
The authors examine the impact of growth of key policy and institutional reforms: macroeconomic stabilization, trade liberalization, deregulation of finance, privatization, deregulation of utilities, modernization of the public sector with a view to increasing its effectiveness and accountability, and the spread of democracy and decentralization. They draw lessons both from a policy and institutional perspective and from the perspective of country experiences about how reforms in each policy and institutional area have affected growth.